Carbon Deposition and Sulfur Poisoning in SrFe0.75Mo0.25O3-δ and SrFe0.5Mn0.25Mo0.25O3-δ Electrode Materials for Symmetrical SOFCs. Issue 9 (1st January 2015) - Zheng, Kun; Świerczek, Konrad; Polfus, Jonathan M.; Sunding, Martin F.; Pishahang, Mehdi; Norby, Truls
Abstract : Redox stable SrFe0.75 Mo0.25 O3-δ and SrFe0.5 Mn0.25 Mo0.25 O3-δ electrode materials were studied in terms of their physicochemical properties and electrochemical performance in symmetrical SOFCs, with focus on their tolerance toward carbon deposition and sulfur poisoning. Both materials possess cubic, B-site cation-disordered Pm -3 m structure in air up to high temperatures. SrFe0.5 Mn0.25 Mo0.25 O3-δ was found to transform to a B-site cation-ordered structure after reduction in dry 5 vol% H2 /Ar at 1100°C, while no structural changes were observed for SrFe0.75 Mo0.25 O3-δ . Weight change upon annealing up to 850°C in air and in dry 5 vol% H2 /Ar indicated an increase in oxygen deficiency on the order of δ = 0.2. Seebeck coefficient and conductivity dependence on the oxygen partial pressure p O2 showed that both oxides exhibit p -type conductivity in air and n -type conductivity under reducing conditions. Carbon deposition was found to depend on temperature, gas composition (CO or CH4 ), and presence of Ce0.8 Gd0.2 O1.9 electrolyte in the composite-type electrode. Stable fuel cell performance, without carbon deposition, was obtained for SrFe0.75 Mo0.25 O3-δ -based SOFC in 10 vol% of CO in CO2 . Also, SOFC operation with CH4 as fuel was achieved without coking at temperatures ≤ 700°C. However, both oxides suffer from sulfur poisoning-related effects in atmosphere with 800 ppm H2 S.